Comparison of generic and specific instruments to assess the quality of life in patients with melasma - Meneguin, Silmara [UNESP]; Mourão, Ioana Bitencourt [UNESP]; Pollo, Camila Fernandes [UNESP]; Miot, Helio Amante [UNESP]; Garuzi, Miriane [UNESP]; Oliveira, Cesar de (Springer Nature, 2022)
Objective: To compare the psychometric performance of a generic and specific instruments in assessing melasma-related quality of life. Methods: A cross-sectional study was conducted with 150 patients with melasma attending an outpatient dermatology clinic of a public hospital in São Paulo state, Brazil. Data were collected using a questionnaire containing sociodemographic and clinical data as well as the generic WHOQOL-BREF, and the dermatological-specific Skindex-16 and HRQ-Melasma. Results: The overall internal consistency of the domains of the three instruments was ≥ 0.7. A strong positive correlation was identified between the Skindex-16 and HRQ-Melasma domains (0.68-0.78). Item-response theory showed that most Skindex-16 and HRQ-Melasma domains were more informative than WHOQOL-BREF. Conclusion: The three instruments for assessing QOL tested presented good psychometric performance, with satisfactory internal consistency values. Only the two dermatological instruments, however, demonstrated a strong correlation between the domains that assess social, emotional, and functional aspects of QOL, indicating that both were able to identify impairments in other QOL dimensions in addition to the physical domain.
Keywords: Melasma; Psychometry; Quality of life; Questionnaire